Aspirin Hypersensitivity in Patients with Coronary Artery Disease: An Updated Review and Practical Recommendations - Luigi Cappannoli; Stefania Colantuono; Francesco Maria Animati; Francesco Fracassi; Mattia Galli; Cristina Aurigemma; Enrico Romagnoli; Rocco Antonio Montone; Mattia Lunardi; Lazzaro Paraggio; Carolina Ierardi; Ilaria Baglivo; et al. (Biomolecules)
Acetylsalicylic acid (ASA) represents a cornerstone of antiplatelet therapy for the treatment of atherosclerotic coronary artery disease (CAD). ASA is in fact indicated in case of an acute coronary syndrome or after a percutaneous coronary intervention with stent implantation. Aspirin hypersensitivity is frequently reported by patients, and this challenging situation requires a careful evaluation of the true nature of the presumed sensitivity and of its mechanisms, as well as to differentiate it from a more frequent (and more easily manageable) aspirin intolerance. Two main strategies are available to allow ASA administration for patients with CAD and suspected ASA hypersensitivity: a low-dose ASA challenge, aimed at assessing the tolerability of ASA at the antiplatelet dose of 100 mg, and desensitization, a therapeutic procedure which aims to induce tolerance to ASA. For those patients who cannot undergo ASA challenge and desensitization due to previous serious adverse reactions, or for those in whom desensitization was unsuccessful, a number of further alternative strategies are available, even if these have not been validated and approved by guidelines. The aim of this state-of-the-art review is therefore to summarize the established evidence regarding pathophysiology, clinical presentation, diagnosis, and management of aspirin hypersensitivity and to provide a practical guide for cardiologists (and clinicians) who have to face the not uncommon situation of a patient with concomitant coronary artery disease and aspirin hypersensitivity.